Photoprotector Effect of Emulsions with Yerba-Mate (Ilex paraguariensis) Extract - Juliana Andriolli Ribeiro; Ederlan Magri; Itamar Luís Gonçalves; Karina Paese; Juliana Roman; Alice Teresa Valduga (Scientia Pharmaceutica, 2023)
Yerba-mate contains in its composition a high concentration of phenolic compounds. This class of secondary metabolites exhibits strong values of molar absorptivity on ultraviolet and visible wavelengths. This study evaluated the effect of yerba-mate extracts on the in vitro solar protection factor (SPF) value of sunscreen formulations. The sunscreen formulations were prepared to have non-ionic lotion as a basis and yerba-mate extract and/or avobenzone as active agents. The SPF and resveratrol protective effect of the formulations were determined by UV-vis spectrometry. A synergic effect between the yerba-mate extract and avobenzone on the SPF was found. Yerba-mate extract at 5% improved the SPF of the avobenzone 5% formulation from 28.46 ± 5.45 to 40.48 ± 0.84. Yerba-mate extract at 5% avoided resveratrol degradation by ultraviolet radiation. At this same concentration, avobenzone produced a smaller effect than yerba-mate extracts in resveratrol protection. The formulations with yerba-mate + avobenzone presented smaller changes in pH values during 12 days of storage. The spreadability profile of yerba-mate and avobenzone formulations was similar to the profile of avobenzone formulations. The results reported here show the suitability of the yerba-mate extract use in photoprotective formulations, highlighting their in vitro effect and opening possibilities for new investigations exploring this property.